NETWORK OF THE MIDDLE EAST NUSANTARA ULAMA (20th Century To 21st Century) - Anri Naldi (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2022)
Abstract. The purpose of this study is to analyze the network of middle eastern ulema of the archipelago from the 20th to the 21st century, the method of line research is qualitative research with a library research approach, namely the literature study which contains a series of theories that are relevant and of course relevant. In the research, the results of this study are the educational background of Indonesia's Leading Ulama (20th century to 21st centuries such as Haji Abdul Malik Karim Amrullah/Buya Hamka (1908-1981 AD) associated with a network of eastern scholars in the middle is Makkah Wahid Hasyim (1914-1953 AD) his studies in Makkah (1932-1933) KH Abdurrahman Wahid/Gusdur (1940-2009 AD) Cairo, Egypt, where he studied (and never finished) at al-Azhar From Cairo, he went to Baghdad to study Arabic literature and culture.His studies in the Middle East lasted until 1971 when he returned to Pesantren Teb uireng belongs to his family. Map of the Middle East Network of Ulama of the 20th to 21st centuries such as Haji Abdul Malik Karim Amrullah/Buya Hamka (1908-1981 AD) clearly came from a network of Middle Eastern scholars from Mecca, Medina and Cairo. Wahid Hasyim (1914-1953 AD) he had studied with a number of well-known scholars in Haramayn, including Sheikh Ahmad al-Nahrawi, Sheikh Sayid Ahmad al-Dimyati, Sheikh Sayid Ahmad Dahlan, and Sheikh Muhammad Khatib al-Hanbali. Abdurrahman Wahid/Gusdur (1940-2009 AD) studied at the Tebuireng pesantren which was founded by KH. Hasyim Asy'ari, who was a student of Muhammad al-Nawawi Al-Bantani and later studied in Cairo, of course al-Azhar met the idea of reforming Jamaluddin al-Afghani, Muhammad Abduh, and Rashid Rida from al-Azhar Cairo. The influence of the Middle East Ulama Network on the understanding and religiosity of Indonesian Muslims such as Haji Abdul Malik Karim Amrullah/Buya Hamka (1908-1981 AD) embraced Muhammadiyah ideology. Wahid Hasyim (1914-1953 AD) and Abdurrahman Wahid/Gusdur (1940-2009 AD) with the understanding of Nahdatul Ulam (NU) in Indonesia. The conclusion of this research is that the Middle Eastern Ulama Nusantara Network has been started since the 17th century until the 19th century from various regions of Malay Indonesia which of course in the 20th to 21st century ulama network is a network that has been formed through the Haramayn route.